IMPLEMENTASI PENGEMBANGAN SUMBER DAYA MANUSIA PADA PERUSAHAAN DAN MANFAATNYA - Ilham Akbar Zulfikar; Fania Mutiara Savitri; M. Sahab; Syifa Varah Lila; Kharom Hija Tuhu (Universitas Haji Sumatera Utara, 2023)
Abstract This article will discuss and analyze the importance of implementing company Human Resource Development (HR), especially in bureaus or travel services that serve the Umrah pilgrimage. This research uses descriptive qualitative method. Data were obtained through interview techniques and literature studies on human resource development in companies. Every company must have workers or employees who are in charge of running the company's operational activities (services). The existence of competition between companies that is increasingly competitive, requires the movers of the company to be more creative, innovative and willing to learn and always make moves so that they continue to experience development. Every company, in this case an Umrah travel agency, needs to have a technology that can support and be useful in carrying out operational activities. In order to optimize the company's service quality, it is necessary to have qualified human resources to mobilize, guarantee and contribute to the smooth operation of the company. Human resources are an important asset for the company because of their central role in the company. As executors of tasks within the company, human resources within the company, namely workers or employees, must be able to make an optimal contribution. To help workers or employees to be able to make an optimal contribution, every company needs to implement development programs either through education or training that will provide opportunities for human resources within the company to continue to improve, develop and enhance individual skills. Human resource development both formally and non-formally is very important for every individual workforce or employee as well as the company. Human resource development is important to increase the ability and knowledge of the workforce or employees so that the company is more competitive both internally and externally and helps build the company's image to a wide audience. It can be seen through research that the umrah travel agency or PT AR RAHMAH TOUR KENDAL has successfully implemented HR development. The results of the study show that human resource development is important for companies because it has a positive influence on service quality and company progress.